Elucidating Volatile Flavor Profiles and Metabolic Pathways in Northern Pike (Esox lucius) During Superchilled Storage: A Combined UPLC-Q-TOF/MS and GC-MS Approach - Shijie Bi; Na Li; Gao Gong; Peng Gao; Jinfang Zhu; Batuer Abulikemu (Foods)
Temperature is the most critical factor in fish preservation. Superchilled storage represents a novel technology that effectively retards quality deterioration in aquatic products. This study investigated the flavor variation patterns and deterioration mechanisms in 16 northern pike (Esox lucius) samples during superchilled storage (−3 °C) based on analysis using gas chromatography-ion mobility spectrometry (GC-IMS) and ultra-performance liquid chromatography–quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS). The results indicate that GC-MS analysis identified 25 key volatile flavor compounds. These comprised seven ketones, thirteen alcohols, aldehydes including 2-methylbutanal, esters such as 2-heptyl acetate and methyl butyrate, as well as nitrogen-containing compounds, exemplified by pyrazines and indole. Non-targeted metabolomics further revealed four pivotal metabolic pathways, glycerophospholipid metabolism, purine metabolism, the pentose phosphate pathway, and arginine biosynthesis. These metabolic pathways were found to regulate flavor changes through modulation of lipid oxidation, nucleotide degradation, and amino acid metabolism. Notably, the arginine biosynthesis pathway exhibited significant correlations with the development of characteristic cold-storage off-flavors, mediated by glutamate accumulation and fumarate depletion. This investigation provided a theoretical foundation for optimizing preservation strategies in cold-water fish species at the molecular level.